Leiurus quinquestratus venom promotes β islets regeneration and restores glucose level in streptozotocin induced type 2 diabetes mellitus in rats - Wesam M. Salama; Sabry A. El-Naggar; Ghada A. Tabl; Nabila I. El-Desouki; Lamiaa M. El Shefiey (Scientific Reports)
Abstract Diabetes mellitus type 2 (T2-DM) is one of the most prevalent chronic metabolic diseases, marked by insulin resistance and a relative lack of insulin production. T2-DM can be treated using various methods; however, these treatments are risky for several vital organs. Subsequently, novel T2-DM replacement therapies should be discovered. The goal of this study was to see how efficient Leiurus quinquestratus venom (LQV) was as a diabetic medicine for the treatment of T2-DM in rats. The median lethal dose (LD50) of LQV has been determined. Then, forty male Sprague Dawley rats were divided into four groups (n = 10) as follows, with group 1 (Gp1) separated as a negative control. Gp2, Gp3, and Gp4 were fed a high-fat diet (HFD) for 12 weeks before receiving an intraperitoneal (i.p) injection of streptozotocin (STZ) as 30 mg/kg b.wt. Gp3 received metformin (Met) as 150 mg/kg b.wt i.p. LQV as 1/40 LD50 was given i.p. to Gp4. Treatments with Met or LQV were once every day for eight weeks. Hematological, biochemical, histopathological, and immunohistochemical studies were determined, along with the percentages of changes in total body weight. Results: LD50 of LQV was 0.3 mg/kg b.wt. Met or LQV treatment reduced hyperglycemia and C-peptide levels and lessened the hepato-renal biomarkers disorders in T2-DM rats. Intriguingly, histological analysis revealed that LQV treatment outperformed Met in improving and restoring β-cells in pancreatic tissues of T2-DM mice. In conclusion, this study demonstrated a new and promising method for treating T2-DM with LQV. Further investigation is required to isolate the bioactive elements from LQV to treat T2-DM.